Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 275917740 species occurrences available in GBIF matching the query: { "Year" : [ "1970-2000" ] } The dataset includes 275917740 records from 16786 constituent datasets: 2 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 14 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 237 records from Nannofossil abundance of Hole 60-458. 10 records from Analyses of the recent components of sediment core PS1277-1. 9143 records from MEXU/Leguminosae. 24 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 2 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 6 records from Potamotrygon boesemani (Chondrichthyes: Myliobatiformes: Potamotrygonidae), a new species of Neotropical freshwater stingray from Surinam. 12 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 5 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 312 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 39 records from A review of the Glossogobius giuris complex in Australia, with wider discussion on nomenclature and possible synonymies. 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 34873 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 407 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 141 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 1 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 40 records from The genus Litophyton Forskål, 1775 (Octocorallia: Alcyonacea: Nephtheidae) from Australia. 4581 records from SEWBReC Bees, Wasps and Ants (South East Wales). 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 9 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 76 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 14 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 1435 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 542 records from COA Bird Collection (Arctos). 88 records from Total foraminifera counts of multinet M33/1_MSN1029. 2162 records from Bryophyte specimens of The Nagoya University Museum. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 20007 records from University of Guam Insect Collection. 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 30 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 298 records from Planktic foraminifera abundance of Hole 32-310. 19 records from Dinoflagellate abundance of Hole 81-554. 118 records from Museu de Ciències Naturals de Barcelona: BGJBB. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 13 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 102 records from Nannofossil abundance of Hole 24-232. 491 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 1305 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 289 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 696 records from MCP-Aves - Coleção de Aves. 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 135 records from Nannofossil abundance of Hole 36-329. 55 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 626 records from Bird specimens of Saitama Museum of Natural History. 79 records from orthopteracollections-nhmj-ioj. 2 records from Carnivores of Syria. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 5 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 5 records from Collections of Bioclass, school #179, Moscow. 159 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 11080 records from BLM CETAP AIR Sightings. 69 records from Mycology collection, Norwegian Forest and Landscape Institute. 5 records from Muséum d'Avignon. 184 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 4 records from Dinoflagellate abundance of Hole 14-144. 2614 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 20 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 4 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 243614 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 8 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 1 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 7 records from Brachymelecta Linsley, 1939, previously the rarest North American bee genus, was described from an aberrant specimen and is the senior synonym for Xeromelecta Linsley, 1939. 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 1 records from UWIZM Anoles. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 1 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 399 records from Pollen analysis of sediment profile TR0 from Truennensee. 2451 records from Macrobenthos Chukchi Sea, 1986. 84 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 274 records from Herbarium of the Institute of the problems of Northern development (TMN). 3 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 5 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 823 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 2 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 48 records from Tardigrad collection of the National Museum of Nature and Science. 1107 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 1120 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 73 records from Faunal assemblage of sediment core TR149-31. 4747 records from Microbial community in marine sediments. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 9224 records from Colecção Entomológica IIA. 15778 records from MZFC/Coleccion de Aves. 43 records from Nannofossil abundance of Hole 10-91. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 35 records from DMNS Egg Collection (Arctos). 215 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 378 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 12206 records from Lepidopterous specimens of Yamagata Prefectural Museum. 411 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 177 records from Happywhale - Humpback Whale in Arctic Ocean. 6 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 47 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 138 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 1 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 193 records from Orthoptera - SMF. 3581 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 3 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 172 records from An updated checklist of aquatic plants of Myanmar and Thailand. 1702 records from BioGIS - Bryophytes - HUJ collections. 40 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 367 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 18171 records from Herbarium Universitatis Daugavpiliensis. 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 658 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 85 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 3 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 306 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 2321 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1263 records from Plecoptera. 10 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 1 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 23798 records from Swan Coastal Plain Survey. 26 records from New Species Of Neoperla Needham And Phanoperla Banks (Plecoptera: Perlidae) From The Philippine Islands. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 9 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 65 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 28 records from Taxonomic And Distributional Notes On Perlesta Teaysia, P. Golconda, And P. Shawnee (Plecoptera: Perlidae). 10 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 581 records from Bees in the UVM Zadock Thompson Zoological Collection. 3 records from NZCS Brownsberg Nature Park Monitoring. 147 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 11277 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 1 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 222 records from Neogene palynomorpha from site 81-552. 131 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 170 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 682 records from RECORD Orthoptera Data. 2 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 25799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 9 records from Oberservation of birds at station PS14/143 along 49° West. 36 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 1 records from Evolution Of Large Carnivores During The Mid-Cenozoic Of North America: The Temnocyonine Radiation (Mammalia, Amphicyonidae). 5266 records from Upper Silesian Museum, Bird Observations. 1556 records from ISM Ichthyology Collection. 103 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 9 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 75 records from Données naturalistes de Quentin ROME. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 50 records from SEWBReC Springtails and allies (South East Wales). 4 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 1549 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 78686 records from The Himalayan Uplands Plant database (HUP Version 1). 9594 records from National Museum of Natural Science. 1642 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 9 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 67 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 1 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1575 records from Hermatypic Corals of Western Australia. 20 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 18 records from Collections ichtyologiques et herpétologiques (BOUM). 4780 records from Données naturalistes de Bruno OGER. 11113 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 3 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 2 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 14305 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 2358 records from NE Scotland fish records 1800-2010. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 336 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 14 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 256 records from bmhs_weatherheadshell_collection. 101 records from Foraminifera species abundances from tow TT011_7-MOC66. 57919 records from Fichier communal des ongulés. 755 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 1 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 11 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 60871 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 2 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 32 records from Living Cirripedia. 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 3 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 473 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 5 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 2 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 19 records from Données naturalistes de Charlotte PICARD. 4 records from Ostracoda abundance of Hole 44-390. 6 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 1 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 3517 records from University of Nebraska State Museum Birds Collection. 5607 records from University of California Santa Barbara Invertebrate Zoology Collection. 116 records from Dinoflagellate cysts of ODP Hole 189-1172D. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 16098 records from Entomology Collection at the Natural History Museum of Utah. 407 records from Planktic foraminifera abundance of Hole 45-395. 968 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 1164 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 602 records from NMML Small Cetacean Aerial Survey 1997. 169854 records from Locations of plants on dot distribution maps in the Flora of Siberia (Flora Sibiraea, 1987–1997). 41759 records from ALCB - Herbário Alexandre Leal Costa. 24 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 9675 records from Fish specimens of Kagoshima University Museum. 26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 4508 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 219 records from The Broward College Insect Collection. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 6 records from Planktic foraminifera abundance of Hole 53-418B. 1651 records from Berea College, Ralph L. Thompson Herbarium. 409 records from Distribution of nanoplankton at trap WR2. 14 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 1 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 6 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 107675 records from Fermanagh Flora. 36915 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 2 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 167 records from Isle of Wight non-native invasive species. 2 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 20 records from Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius. 2140 records from Weber State University Herbarium. 190 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 1 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 125 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 368 records from UNCW Aerial Survey 1998-1999. 351 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 84 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 79 records from Diatom abundance of Hole 95-613. 36 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 23 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 6 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 1 records from Diura Washingtoniana (Hanson) Resurrected From Synonymy With D. Nanseni (Kempny) (Plecoptera: Perlodidae), Supplemented With A Description Of The Larva And Egg And Comparison To Other Congeners. 2148 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 23 records from Abundance of benthos infauna at station GIK23042-2. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 1494 records from SIM-Fungal records compiled by Joan Montón. 276055 records from Western Australian Museum provider for OZCAM. 352 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 2 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 3979 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 419 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 1141900 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 208288 records from NRW Regional Data: South East Wales Non-sensitive species. 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 19 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 59788 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 13 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1502 records from M. Gollop Collection. 26746 records from Naturalis Biodiversity Center (NL) - Diptera. 95 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 4 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 1 records from A new aquatic beetle family, Meruidae, from Venezuela (Coleoptera: Adephaga). 10 records from Grewia hispidissima Wahlert, Phillipson & Mabb., sp. nov. (Malvaceae, Grewioideae): a new species of restricted range from northwestern Madagascar. 1 records from Plant-parasitic nematodes of Republic of Karelia. 4 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 453 records from Benthic foraminifera counts of sediment core PS1852-2. 2099 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 3012 records from Distribution of foraminifera of sediment core GIK23258-2. 76 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 2 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 3 records from Six new species of Orthochirus Karsch, 1892 from Iran (Scorpiones Buthidae). 19 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 103658 records from University of Minnesota Insect Collection. 157540 records from ARABEL - Arachnologia Belgica. 74296 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 11346 records from Arctic Species Trend Index (ASTI) : Marine. 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 24735 records from Wolli Creek Preservation Society Bird Survey. 552 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 207 records from MLZ Bird Collection (Arctos). 25 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 4 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 11 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 2562 records from Gastropod Specimens of the Yamagata Prefectural Museum. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 30 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 22725 records from Herbarium Senckenbergianum (FR) - Fungi. 1942 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 2 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 624 records from Plant specimens of Bihoro Museum. 1640 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 96 records from Planktic foraminifera counts at CTD station PS55/063. 77 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 150 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 631 records from Leicestershire and Rutland Aculeate Records. 11 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 172 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 205312 records from First Bird Atlas. 3 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 5 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 28 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 13794 records from Herbier Louis-Marie (QFA) - Collection de lichens. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 73 records from Planktic foraminifera abundance of Hole 49-409. 171 records from Planktic foraminifera abundance of Hole 29-284A. 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 345441 records from Plant. 79 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 3 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 51 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 4 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 1905 records from MMS Marine Mammal Survey, PNW 1989-1990. 11 records from Reptilia ZMK. 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 5242 records from United Kingdom National Whale Stranding Database 1913-2008. 138 records from The bees of Lebanon (Hymenoptera: Apoidea: Anthophila). 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 1 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 12 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 899 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 7960 records from Inventario de Hymenóptera; parasítica en México. 327 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 4 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 2302 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 659 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 26 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 11 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 47 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 30 records from Nannofossil abundance of Hole 24-233A. 1 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 24 records from Dinoflagellate abundance of Hole 28-274. 32 records from Total foraminifera counts of multinet FCA97C_MSN1345. 34 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1 records from Catalogue and description of the coccolithophores (Haptophyta, Coccolithophyceae), calcareous, scale-bearing microalgae, in New Zealand waters. 65 records from Birds Specimens of Akita Prefectural Museum. 1 records from Three endemic Aphaenogaster from the Siculo-Maltese archipelago and the Italian Peninsula: part of a hitherto unrecognized species group from the Maghreb? (Hymenoptera: Formicidae: Myrmicinae). 103885 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-78. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 2250 records from MSUM Ichthyology and Herpetology Collections. 185 records from Size of planktic foraminifera at CTD station PS55/051. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 41 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 616 records from Whale catches in the Southern Ocean. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 10 records from Benthic macrofauna abundance of sediment core 13200-008. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 4530 records from ERBG AVH data. 10 records from CABI Africa Invasive and Alien Species data. 451 records from River Biologists' Database (EPA). 16 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 5 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 79659 records from Tiroler Landesmuseum Ferdinandeum. 39 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 11428 records from Communautés adventices des systèmes cotonniers du nord Cameroun. 10 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 1791 records from Odonata records from RSPB Reserves 1970-2009. 4 records from Données supplémentaires Atlas des Mammifères marins. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 132 records from Abundance of radiolaria at station UT99-23-2. 503102 records from NBIS Records to December 2016. 25 records from Planktic foraminifera abundance of Hole 51-417B. 1421 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 372 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 495 records from South American Antarctic Marine Biodiversity Literature. 1335 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 4 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 3 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 638 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 668 records from California State University, Long Beach Birds. 22 records from Ostracoda abundance of Hole 24-238. 1 records from Thirteen new records of ferns from Brazil. 32 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 15 records from Meiofauna abundance in sediment core 54301-010. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 76026 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4336 records from NE Scotland other invertebrate records 1800-2010. 12 records from Coleccion Briologica 3T 2020. 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 2 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 3 records from Review of the millipede family Haplodesmidae Cook, 1895, with descriptions of some new or poorly-known species (Diplopoda, Polydesmida). 9 records from Ameroculodes miltoni, a new species of estuarine amphipod (Crustacea: Malacostraca: Peracarida: Oedicerotidae) from the southeastern United States. 10 records from The Brazilian Goblin Spiders Of The New Genus Predatoroonops (Araneae: Oonopidae). 9 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 3587 records from Données Entomologiques A. HORELLOU 1988-2018. 321 records from Foraminifera abundance of Hole 74-526A. 184 records from Dinoflagellate abundance of Hole 81-555. 5 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 4 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 797 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 63 records from Records of Halicarcinus planatus at sub-Antarctic regions. 5 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 71 records from Herbier National de Guinée (HNG). 19 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 1000 records from Iowa State University Fishes Collection. 1886 records from Global compendium of Aedes albopictus occurrence. 49 records from Nannofossil abundance of Hole 27-259. 6 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 11 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 232 records from Planktic foraminifera abundance of Hole 21-207. 8 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 23 records from Benthic foraminifera abundance of Hole 93-603. 7630 records from WOLL AVH data. 3904 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 84 records from Ostracoda abundance of Hole 48-403. 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 22 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 2227 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 1589 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 182 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 576 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 4614 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 1360 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 2 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 1 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 314 records from Foraminifera abundance of Hole 64-481. 8 records from Données des collections d'algues du MNHN. 1 records from Replacement names and nomenclatural comments for problematic species-group names in Europe's Neogene freshwater Gastropoda. 1862 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 9784 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 214 records from Coléoptères Silphidés du département du Loiret. 149 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 123 records from Total foraminifera counts of multinet M21/2_MSN648. 258251 records from NOAA AFSC North Pacific Groundfish Observer. 2197 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 4 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 9303 records from UTEP Invertebrates (Arctos). 597 records from Diptera Collection of Museum and Institute of Zoology PAS. 80 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 88 records from Fish occurrence in Kuban River basin. 1 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 163 records from Relative abundance of coccosphere-units at site GIK23414. 379 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 2 records from Planktic foraminifera abundance of Hole 19-191A. 23643 records from CNIN/Abejas de México/Apoidea. 915 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 1521 records from Flora útil del Municipio de la Huerta, Jalisco. 1075 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 57 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 634 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 409 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 151 records from Total foraminifera counts of multinet M36/6_MSN1196. 13 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 10 records from Mangelia (Gastropoda, Conoidea) species of the Turkish coasts with description of Mangelia vanaartseni sp. nov.. 1 records from Revision of the spider genus Ischnocolus Ausserer, 1871 (Mygalomorphae: Theraphosidae: Ischnocolinae). 1 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 15 records from Nannofossil abundance of Hole 10-93. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 2997 records from MMS Seabird Ecology Study 1985. 3 records from Six new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 2 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 2 records from A new species of Diplotaxodon (Cichliformes: Cichlidae) from Lake Malaŵi. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 90 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 11 records from Benthic macrofauna abundance of sediment core 13077-093. 1 records from Invasive Non-Native Species, Outer Hebrides. 221256 records from Phase 2 Lowland Grassland Survey of Wales. 24775 records from Naturalis Biodiversity Center (NL) - Crustacea. 1 records from Brown algae specimens of Komatsu City Museum. 2723 records from Danish Ants (Formicidae). 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 12 records from A new species of Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio Tocantins-Araguaia basin, Brazil. 330 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 5 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 19872 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 99360 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 201898 records from DATAVES. 7 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 7 records from Revision of the genus Neozavrelia Goetghebuer, Thienemann, 1941 (Diptera Chironomidae) from Eastern Siberia and the Russian Far East, with the description of new species. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 64 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 100 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 3 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 3 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 115 records from Total foraminifera counts of multinet M21/4_MSN694. 211 records from Planktic foraminifera abundance of Hole 14-142. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 722 records from Insects, Outer Hebrides. 13 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 59 records from Nannofossil abundance of Hole 73-521A. 1036 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 954 records from BioGIS - Vascular plants - Israeli Gene Bank. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 2 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 3 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 9990 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 2 records from Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India. 526 records from Range table from benthic foraminifers in ODP Hole 151-913B. 7 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 495 records from Radiolaria assemblage in sediment core GIK23414-6. 308 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 138 records from Myxomycetes collection of the University of Eastern Finland. 24 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 9752 records from Seasearch Marine Surveys in England. 27 records from Planktic foraminifera abundance of Hole 84-566C. 1 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 4 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 9 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 2 records from The genus Stenoterommata Holmberg, 1881 (Araneae, Pycnothelidae) in the Cerrado and Atlantic Forest from Southeastern and Central Brazil: description of four new species. 4802 records from Collection Trichoptera - SMF. 16 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 110 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 1200 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 99 records from Planktic foraminifera abundance of Hole 27-262. 1910 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 1 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 27 records from Planktic foraminifera abundance of Hole 27-260. 1984 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 44836 records from Arizona State University Hasbrouck Insect Collection. 63364 records from CCAMLR historic KRILL. 42 records from Collection Strepsiptera SMF. 62 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 1731 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 1 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 12 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 156 records from Chironomid remains in the sediment sequence of Site PG1212. 2812 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 2277 records from Lista florística de la Costa Grande del estado de Guerrero. 3 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 2 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 32444 records from MDFRC macroinvertebrate survey. 36 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 72 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 5 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 83 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 32 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 16 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 24 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 58 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 6 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 3 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 180 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 4 records from Catalogue of the Syrphidae of Egypt (Diptera). 79 records from Nannofossil abundance of Hole 31-299. 6695 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 49 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 122 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 1 records from Morphological systematics of kingsnakes, Lampropeltis getula complex (Serpentes: Colubridae), in the eastern United States. 336 records from K-State Museum of Entomological and Prairie Arthropod Research. 18890 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 67 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 1 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 16 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 214 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 4814 records from The Dolphin Project. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 65 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 678 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 400 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 12 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 247 records from Etude floristique de la forêt marécageuse de Lokoli au Bénin. 22 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 11877 records from Données naturalistes de Monsieur François FOURNIER. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 912 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 23493 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 1 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 39 records from Planktic foraminifera abundance of Hole 14-137. 97349 records from Hatikka Observation Database. 189 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 45 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 93909 records from inatura - Erlebnis Naturschau Dornbirn. 168 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 1280 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 130 records from Total foraminifera counts of multinet M21/6_MSN784. 49 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 1205 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 10 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 2558 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 917 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 30460 records from Insect specimen database of Atsugi City Museum. 38 records from Nannofossil abundance of Hole 10-89. 8523 records from Nematoda of Costa Rica (INBio). 91 records from Nannofossil abundance of Hole 30-285A. 58 records from A Revision of the Nearctic Predaceous Midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae). 2 records from Revision of the family Acidopsidae Števčić, 2005, and the systematic position of Typhlocarcinodes Alcock, 1900, Caecopilumnus Borradaile, 1902, and Raoulia Ng, 1987, with descriptions of two new genera and five new species (Crustacea: Brachyura: Goneplacoidea). 356 records from Morphologische Daten von Puffinus creatopus. 20082 records from WTSWW Data: All Taxa (West Wales). 364 records from Lucanidae. 52 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 173752 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 133 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 100143 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 181984 records from South Australian Museum Australia provider for OZCAM. 2 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 31 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 3 records from Coccolith counts of multinet M32/5_MSN981. 78 records from Herbarium BSG Hepaticopsida. 5 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 51 records from Brock University Herbarium (BU). 160 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 117 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 2857 records from Whicher Scarp Flora Survey. 354 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 2 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 41 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 11 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 110 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 278 records from Gomex Sperm Whale Survey 2000. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 67 records from Modernisation des ZNIEFF du PnrL. 7 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 1 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 92 records from Registros Primates Neotropicales Convocatoria APC. 2 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 1 records from A new genus and species of pigeon (Aves, Columbidae) from the Kingdom of Tonga, with an evaluation of hindlimb osteology of columbids from Oceania. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 13 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 11 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 532 records from La familia Asclepiadaceae en México. 9 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 32 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 180 records from Benthic foraminifera abundance of Hole 41-366A. 1 records from Otter survey of Ireland 2004 & 2005. 1052 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 14 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 7 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 177 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 128 records from Total foraminifera counts of multinet POS247/2_MSN1386. 364 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 10079 records from CSIRO, fish surveys by the Soela, 1980s. 796 records from Microfossil abundance of Hole 16-158. 342 records from Nannofossil abundance of Hole 78-543. 11311 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 408 records from Glasgow Museums BRC: Chrysomelidae. 8 records from New Species And Records Of Anacroneuria (Plecoptera: Perlidae) From Ecuador And Paraguay. 30 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 23 records from Total foraminifera counts of multinet FCA97C_MSN1339. 34 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 28 records from Bryde’s whales off eastern Venezuela - Vessel 1978-1979. 2540 records from USAC Mammals Collection. 361 records from Nannofossil abundance of Hole 66-490. 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 193 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 6 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 1568 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 146 records from Fossil Specimens of Komatsu City Museum. 478 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 445 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 174 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 1516 records from Données naturalistes de Bernard Lalanne-Cassou. 27 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 2 records from PSUZC-Reptile Collection. 33 records from Planktic foraminifera counts of sediment core RC13-154. 820 records from Nannofossil abundance of Hole 82-558A. 2 records from A new water mite species of the Hygrobates fluviatilis-complex from Russia (Acari Hydrachnidia, Hygrobatidae). 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 392 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 36 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 1497 records from BioGIS - Mammals - SPNI. 20 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 9558 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 13 records from Diatom abundance of Hole 60-460. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 160 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 75284 records from SEWBReC Birds (South East Wales). 76 records from Lepidoptera of Mordovia State Nature Reserve. 130 records from Total foraminifera counts from multinet SO119_MSN1285. 8 records from New species of the Neotropical genus Campatonema Jones (Geometridae, Ennominae) with the first description of the female. 22 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 289 records from Planktic foraminifera abundance of Hole 42-372. 1970 records from Dipterists Forum: Field Week 1981 (Kent). 2744 records from MEXU/Flora de Oaxaca. 4951 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 4 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 2 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 2701 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 207 records from Nannofossil abundance of Hole 66-488. 83 records from Heavy minerals of sediment core PL94-64. 74648 records from Amphibiens et Reptiles de France (Enquête 2). 88 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 3 records from Notes on Oriental Clivinini and the description of two new species (Coleoptera: Carabidae: Clivinini). 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 66 records from Données naturalistes d'Alain BERLY. 8382 records from Herps Specimens. 29998 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 14 records from Données opportunistes. 752 records from Red-throated diver national surveys in Scotland - raw data. 1960 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 368 records from Ring ouzel national sample survey in the UK in 1999. 15 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 60 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 4 records from Inventaire et regroupement de données Natura 2000. 1015 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 30722 records from Données de la flore d’Alsace (SBA). 4 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 3 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 3 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3226 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 200 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 7 records from Transcription of selected miombo timber species of a floristic inventory in Cuando-Cubango, Angola. 1723 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 124 records from Kirkliston Range stream monitoring. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 77 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 13 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 12519 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 1195 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 1 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 2763 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 12 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 60 records from Total foraminifera counts from M35/1_MSN1065. 1524 records from Marine Turtles. 62 records from Foraminifera abundance of Hole 33-317A. 549 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 25 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 3 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 10 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 2 records from Vermont Orthoptera Records from Historic Dot Maps. 98 records from Nannofossil abundance of Hole 67-499B. 5 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 1788 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 2 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 93 records from Marine algal (seaweed) flora of Faial Island, Azores. 182 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 2385 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 63 records from données araneologiques de LEENKNEGT Virginie. 24 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 2 records from Herbarium Senckenbergianum (FR) - Protista. 12 records from Colección de helechos de la FML. 107 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 76 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 13605 records from Données de l'Observatoire de la Faune de Bourgogne. 848 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 1074 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 3 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 546 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 239 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 2118 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 36 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 54 records from Echinoderms from the Seaflower Biosphere Reserve. 3 records from Volutellonectria (Ascomycota, Fungi), a new genus with Volutella anamorphs. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 10 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 117 records from Nannofossil abundance of Hole 49-408. 130412 records from Allan Herbarium (CHR). 17 records from Analyses of the recent components of sediment core PS1011-1. 58845 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 45 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 13902 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 4 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 682 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 2 records from MVZ Herp Observations (Arctos). 306 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 145 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 6 records from Foraminifera abundance of Hole 58-442. 4 records from New Species Of Tyloperla (Plecoptera: Perlidae) From Vietnam And Thailand. 627 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 2 records from Coleção de Coleoptera da Universidade de Brasília. 4196 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 766 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 9 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 4575 records from Marie-Victorin Herbarium (MT) - Bryophytes. 18 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 113 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 417 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4). 142680 records from National Benthic Inventory. 16 records from Phenological Center - Fishes (Murmansk). 109 records from Dinoflagellate cysts from sediment core PS1295-4. 2 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 111 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 1071 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 8 records from Exotic speciments butterflies at Museum Zoologi Bogor, Indonesia. 183 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 3 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 8332 records from Scotland Otter Survey Database. 548 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 2 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 193496 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 145 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 51265 records from CAS Entomology (ENT). 24 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 3154 records from Carnet B Lorraine. 33380 records from Naturalis Biodiversity Center (NL) - Pisces. 21 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 448 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 320 records from Marine algal (seaweed) flora of Formigas Islets, Azores. 5 records from Nannofossil abundance of Hole 16-157A. 387 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 375 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 51 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 384 records from Nannofossil abundance of Hole 17-167. 47 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 3 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 1666 records from Distribution of major planktic foraminifer at Site 177-1090. 121 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 102 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 172 records from checklist-of-birds-of-zomba-mountain. 9 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 65494 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 6 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 2 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 3402 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 1200510 records from Flore Franco-Belge. 33111 records from EAC - Herbário Prisco Bezerra. 212 records from East Ayrshire Species Database. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 1136 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 735 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 174 records from Planktic foraminifera abundance of Hole 22-217. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1694 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 2 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 40 records from LPO_PACA_2017_12_18. 8 records from Nannofossil abundance of Hole 39-353A. 216 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 11 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 109 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 3340 records from Census of species recorded during phytosociological surveys in Benin. 1251 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 589 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 391 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 3468 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 1 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 18 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 2952 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 75 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 9627 records from Collection Pisces SMF. 178 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 4041 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 11 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 2931 records from MEXU/Tipos de plantas vasculares. 15 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 36 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 283 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 5098 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 51 records from Total foraminifera counts from M35/1_MSN1051. 24 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 49 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 488 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 59 records from Seabird and cetacean sightings from Cruise SY002 of RV Shoyo Maru, Tropical Atlantic Ocean, Oct. 2000. 6 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 119 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 201 records from Total foraminifera counts of multinet M21/1_MSN606. 522 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 2045 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 23494 records from Estonian Nature Observations Database. 6 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 12 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 1 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 34880 records from Botanical Museum, Copenhagen, Mycology Herbarium. 6503 records from NCSM Mammalogy Collection. 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 41 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 1 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 25489 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 6 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 25438 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 5 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 32 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 2 records from Planktic foraminifera counts of multinet PS2616-5. 16 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 322 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Xiloteca). 13251 records from Fife Nature Records Centre combined dataset. 63 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 1 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 1 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 20 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 6 records from Review of the genus Macropsis Lewis, 1836 (Homoptera: Auchenorrhyncha Cicadellidae: Eurymelinae: Macropsini) of Southeastern Kazakhstan with description of new species. 34 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 5781 records from Odonata de Veracruz. 85 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 224 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 217 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 966 records from Planktic foraminifera abundance of Hole 18-173. 83 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 213 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 1 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 2 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 17 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 4096 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 9 records from The Winter Stoneflies (Plecoptera: Capniidae) Of Mississippi. 191 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 44 records from Collection Ephemeroptera - SMF. 5 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 44 records from Microzooplankton abundance and biomass at station TT045_15-2. 3403 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 11 records from A survey of small mammals in the Volta Region of Ghana with comments on zoogeography and conservation. 12037 records from Denver Museum of Nature & Science - Entomology. 1 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 19245 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 15 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 33 records from UWIZM Cnidarians. 24 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 186 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 52267 records from Tasmanian Museum and Art Gallery provider for OZCAM. 422 records from TTRS Mammals. 3 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 6 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 10 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 3 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 2 records from Benthic foraminifera abundance of Hole 42-376. 411 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 865 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 26 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 4 records from A new species of Thamnodynastes Wagler, 1830 from western Amazonia, with notes on morphology for members of the Thamnodynastes pallidus group (Serpentes Dipsadidae, Tachymenini). 22525 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 261 records from University of Sindh Jamshoro Herbarium. 17 records from A New Genus of the Spider Family Caponiidae (Araneae, Haplogynae) from the West Indies. 27 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 8 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 89 records from Faunal assemblage of sediment core TR149-32. 516 records from Nannofossil abundance of Hole 15-149. 146 records from Database for alien invasive plants occurrences in Germany. 13 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 12 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 6202 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 172 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 62 records from Benthic foraminifera abundance of Hole 84-566C. 407 records from Strathclyde badger sett surveys 1996-2000. 454 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 871 records from SEFSC Southeast Cetacean Aerial Survey 1992. 9085 records from OUPR - Herbário "Professor José Badini". 10 records from Nannofossil abundance of Hole 58-442B. 16 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 23348 records from National Biodiversity Data Bank. Observation records, 1900-2014. 156 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 15 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 3316 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 3 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 119475 records from Larvae of decapods off Portuguese coast from 1986 to 1994. 1656 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 1313 records from Diatom assamblage in samples from sediment trap OG5. 3 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 5 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 2487 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 463 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 1269 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 1 records from Révision du genre Paradorodocia Machatschke, 1957 (Insecta, Coleoptera, Rutelidae, Adoretinae). 1 records from Distributional and taxonomic notes on the crab spider genus Talaus Simon, 1886 with description of a new species (Araneae: Thomisidae). 85616 records from MICROBIS database. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 58 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 4 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 4712 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 102178 records from Swiss National Grasshoppers Databank. 244 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 64 records from Planktic foraminifera counts at CTD station PS55/083-1. 2845 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 133 records from Pollen profile II/B at Krumbach, Germany. 21798 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 1685 records from Weevil and Bark Beetle records via iRecord. 13 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 17 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 5 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 677 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 66 records from Planktic foraminifera abundance of Hole 22-212. 210 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 173 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 19 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 1998 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 138 records from Wichita State University Collection. 26989 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 58 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 1 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 4 records from Taxonomic review of the genus Assamacris (Orthoptera: Acrididae: Catantopinae) with a new species and a newly discovered female. 173 records from pbzt_insect_biodiversity. 245 records from NZCS Upper Tapanahony Expedition 1991. 3 records from A taxonomic revision of Otomantis Bolivar, 1890 (Mantodea: Hymenopodidae, Acromantinae) with description of five new species. 152 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 9 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 804 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 1 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 31945 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 1 records from Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China. 8 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 1 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 40 records from Coleção de Nematoda do Museu Nacional - UFRJ. 398 records from Inventory of plant species through Benin (West Africa). 5 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 1 records from The bee genus Caenaugochlora (Hymenoptera, Apoidea) and its constituent subgenera, with new species of Caenaugochlora s. str. from Ecuador. 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 69 records from Total foraminifera counts of multinet M21/5_MSN731. 3 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 2 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 966 records from Planktic foraminifera abundance of Hole 72-516F. 1648 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 1 records from Benthic foraminifera abundance of Hole 96-624. 3274 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 13 records from Four new species of Pomphopsilla Jałoszyński in Rwanda, Burundi and DR Congo (Coleoptera: Staphylinidae: Scydmaeninae). 263 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 6 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 2643 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 20 records from Nouveautés dans le genre Lomariopsis Fée (Pteridophyta, Lomariopsidaceae) à Madagascar: trois espèces nouvelles et une espèce africaine nouvellement signalée. 2729 records from Fungi specimens of Saitama Museum of Natural History. 1055 records from Mollusca Collection of Saitama Museum of Natural History. 1 records from Description of Gondwanoscurus curleri sp. nov. from the West Usambara Mts, Tanzania (Diptera: Psychodidae). 54 records from Siphonoecetinae (Crustacea: Amphipoda: Ischyroceridae) 7: Australian Concholestids, Ambicholestes n. gen., with a Description of Six New Species, and a New, Restricted Diagnosis for Caribboecetes Just, 1983. 631 records from Planktic foraminifera abundance of Hole 72-518. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 1 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 605 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 417 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 781 records from Bosque Mesófilo de Montaña de México. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 785 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 24558 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 1 records from Happywhale - Crabeater Seal in Southern Ocean. 19 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 1 records from Collection ornithologique A. Maës. 401 records from Planktic foraminifera distribution of sediment core SU81-07. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 3790 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 30 records from Mammal specimens of Komatsu City Museum. 113 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 9158 records from National Stag Beetle Surveys (Great Stag Hunts). 1734 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 466 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 12 records from Benthic foraminifera abundance of Hole 96-620. 99 records from Nanoplankton abundance at station GeoB2006-4. 16 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 4824 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 2 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 18 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 26 records from Leif Richardson Vermont Bee Specimens. 15 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 153 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 1817 records from Collection Crustacea - ZMB. 174 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 643 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 11 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 14 records from Nannofossil abundance of Hole 25-249. 66 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 4 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 2079 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 22 records from Three new species and six new records of Scathophagidae (Diptera) from Japan with a key to the Japanese genera. 3 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 430 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2310 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 2 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 5 records from Three new species and new records of cuckoo bees of the genus Epeolus in Turkey (Hymenoptera: Apidae: Nomadinae). 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 55 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 6 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 45872 records from The national database for marine data (MADS). 30 records from Nannofossil abundance of Hole 9-82. 171 records from Foraminifera abundance of Hole 57-440A. 37 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 1948 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 3 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 74 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 97 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 66 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 109 records from Planktic foraminifera abundance of Hole 18-181. 3 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 165 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 5751 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 71 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 1230 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 12 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 190 records from Leicestershire and Rutland Mature trees Inventory 2011. 331 records from Pollen data of trap CB4. 20 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 1 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 21 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 80 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 2 records from Microfossil abundance of Hole 21-208. 1680 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 150 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 333 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 24926 records from Plan de vertebrados de la Patagonia. 4 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 2954 records from Distribution of planktic foraminifera of sediment core M35003-4. 125881 records from Herbarium of Taiwan Forestry Research Institute. 1 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 4 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 5760 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 221 records from Données odonates. 165 records from Malawi-Histeridae-Biodiversity-Data. 15812 records from Swiss National Diplopoda Databank. 24155 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 718 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 11 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 33 records from Benthic foraminifera and algae abundance of Hole 35-325. 34 records from Microzooplankton abundance and biomass at station TT043_4-1. 85 records from (Fig. 4) Nannofossil abundance of Cretaceous profile Pré-Guittard, SE France. 115 records from Distribution of seabirds at sea in the Gulf of Carpentaria, Australia (1990-1991). 5 records from Further Descriptions Of Western North American Podmosta Larvae And Their Separation From Ostrocerca Larvae (Plecoptera: Nemouridae). 1794 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3249 records from Benthos counted on dredged samples during Valdivia cruise VA53. 1 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 24237 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 32 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 214 records from Total foraminifera counts of multinet M21/1_MSN608. 8 records from The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa. 160 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 212 records from Planktic foraminifera abundance of Hole 84-567A. 8 records from Cladistic analysis and synopsis of Chloropepla Stål (Hemiptera: Heteroptera: Pentatomidae) with the description of three new species. 1242 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 74 records from Nannofossil abundance of Hole 39-359. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 14 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 32 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 113 records from Nannofossil abundance of Hole 49-412. 24 records from Abundance of benthos infauna at station PS1240-1. 608 records from Marine algal flora of Flores and Corvo Islands, Azores. 767 records from Mediterranean seabird surveys 99/00/02. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 29 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 12 records from Microzooplankton abundance and biomass at station NBP97-03-12-2. 707 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 425 records from données arachnologiques de CARR David. 6 records from A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil. 140 records from (Table 2) Distribution of selected planktonic foraminifer species at ODP Site 124-770. 47451 records from HUEFS herbarium - Universidade Estadual de Feira de Santana - Herbário Virtual REFLORA. 19 records from Musée Vert ornithology collection. 39 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 3 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 1170 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 357 records from Feeding rhythms of the common goby Pomatoschistus microps at the brackish tidal marsh 'Het verdronken land van Saeftinge' in 1994. 21407 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 2 records from New taxa and new records of Erythroneurini from China (Hemiptera: Cicadellidae: Typhlocybinae). 4725 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 4 records from Two new species of Carcinoplax H. Milne Edwards, 1852, and Pycnoplax Castro, 2007, from the western Pacific, and a description of the female of Thyraplax truncata Castro, 2007 (Crustacea, Decapoda, Brachyura, Goneplacidae). 1740 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 7 records from Planktic foraminifera abundance of Hole 94-611B. 1403 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 1 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 4 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 2143 records from Range table from benthic foraminifers in ODP Hole 154-929A. 165 records from Nannofossil abundance of Hole 30-286. 2 records from Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution. 11 records from Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan. 46667 records from Derek Lott Coleoptera Dataset. 16603 records from JCT AVH data. 33115 records from University of Tennessee Bryophyte Herbarium. 5075 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 33 records from Planktic foraminifera counts of sediment core V28-128. 710 records from Likona Invertebrates. 67 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 22 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 128888 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 431 records from Amphibiens de Guyane. 57 records from Planktic foraminifera abundance of Hole 62-465. 11 records from Nannofossil abundance of Hole 9-82. 8 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 3 records from Planktic foraminifera abundance of Hole 20-200A. 575 records from Nannofossil abundance of Hole 75-530A. 98 records from Acoustic detections from research cruises in the Med sea, 1994-2001. 2896 records from DBRC Hemiptera species records 1969 to 2015. 1 records from Collection Myriapoda - SNSD. 57678 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1035 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 4 records from Revision der Gattung Agachila D & G - M, 1954 (Hemiptera: Heteroptera: Tingidae). 699 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 39 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 2887 records from Dorset SW Pilot species dataset. 72 records from Contrasting species diversification of Eutarsopolipus (Acariformes: Podapolipidae) on Castelnaudia and Notonomus (Coleoptera: Carabidae). 42 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 9 records from Benthic macrofauna abundance of sediment core 13077-087. 96 records from (Table 2e) Nannofossil distribution chart of petroleum well Leeuwin-1. 1801 records from MCCC - Mendocino College Coast Center Herbarium. 992 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 139 records from Nannofossil abundance of Hole 24-237. 3268 records from Cumbria Non Native Invasive Species. 1 records from Review of the Stenoscelidea complex and key to the known genera of Stenoscelideini (Hemiptera: Heteroptera: Coreidae). 459 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 90 records from Mollusc collection Natuurmuseum Brabant, Tilburg. 317 records from Benthic foraminifera and algae abundance of Hole 81-554A. 4 records from New species of Langona Simon, 1901 and Neaetha Simon, 1884 (Araneae Salticidae) from Thailand. 982 records from Diatom assamblage in samples from sediment trap OG4. 430 records from DAR AVH data. 94004 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 349 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 41 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 8 records from Microzooplankton abundance and biomass at station TT050_17-4. 1 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 433 records from DBL_Life. 258 records from Océanopolis mammifères marins en Bretagne 1993-2015. 7 records from Studies of the genus Anthelephila Hope (Coleoptera: Anthicidae). Part 19. New species from Indonesia and Malaysia. 13339 records from BLS Rare and Threatened Lichen Records: England. 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 16 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 78 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 1 records from Two new species of Nyctelia Latreille (Coleoptera: Tenebrionidae) from Argentinean Patagonia with zoogeographical and ecological remarks. 1 records from Two new species of Corynellus Bates, 1885 (Coleoptera: Cerambycidae: Cerambycinae). 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 9 records from Taxonomic review of Coccobius species (Hymenoptera: Aphelinidae) from China, with notes on their use in biological control of scale insect pests (Hemiptera: Diaspididae), and description of a new species. 414 records from Percentages of planktonic foraminifera species in sediment core V30-40. 34 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 245 records from Nannofossil abundance of Hole 37-333. 3 records from Amoeboid protists isolated from ancient Siberian permafrost. 2487 records from Inventaire des Mollusques Sphaeriidae de France. 3186 records from données aranéologiques de CORNIC Jean-François. 32 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 2424 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 69 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 1028 records from Nannofossil abundance of Hole 94-607. 35 records from Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae). 1010 records from Thrips (Thysanoptera) in Norway. 121 records from Mammalian Specimens of the Yamagata Prefectural Museum. 34 records from BID-Malawi-Arctiidae-Biodiversity-Data. 21 records from Bird specimens of Ryukyu University Museum (Fujukan). 1098 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 23 records from Weevils of Poland. 2 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1171 records from Arachnida of Costa Rica (INBio). 2429 records from Ross A. Layberry, Collection. 67 records from Occurrence of some antimalarial plants from Cameroon. 23 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 1 records from Niuailan, a new genus to accommodate Carneoryctes peterseni (Endrődi, 1967) (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) from New Ireland, Papua New Guinea. 35 records from Royal Belgian Institute of Natural Sciences marine Chelicerata collection. 668 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 197 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6. 92 records from Microfossil abundance of Hole 50-416A. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 4 records from Microplankton abundance at bottle station SEPT-1999-K7. 3 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 1 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 20 records from Revision of Nearctic Paramyia Williston (Diptera: Milichiidae). 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 1 records from A new flower fly species of Cepa Thompson & Vockeroth (Diptera: Syrphidae) from the Valdivian evergreen forest hotspot, Chile. 62 records from Coleccion de helechos de la FML. 35 records from Quoll sightings register for Nth QLD. 4 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 21 records from Highland biodiversity of Fanniidae (Insecta, Diptera): fourteen new species from the Andes and Central America. 91287 records from University of Florida Invertebrate Paleontology. 15 records from Review, cladistic analysis and biogeography of Nezara Amyot & Serville (Hemiptera: Pentatomidae). 170319 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 407 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 448 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 9 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 63 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1362. 6974 records from Inventaire des Ephémères de métropole (Opie). 65 records from Tetrápodos de Uruguay. 159 records from (Table 2) Range chart of benthic and planktonic foraminifera of ODP Site 127-794. 18 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 9 records from A revision of the bee genus Ancyloscelis (Hymenoptera: Apidae) in Argentina. 4268 records from Phenology and biological traits of adult migrating atlantic salmon (Salmo salar) sampled by trapping in the survey in the Nivelle river (France). 21 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 12 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 20 records from The Haliplidae (Coleoptera) of Atlantic Canada: new records, distribution, and faunal composition. 7086 records from University of Kentucky Insect Collection. 47068 records from Atlas des Orthoptères et Mantides de France métropolitaine. 23 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 251 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 13455 records from UAM Bird Collection (Arctos). 4 records from Six new species of the Oriental genus Hlavaciellus Jałoszyński (Coleoptera Staphylinidae, Scydmaeninae). 2 records from A new species of Eremias (Squamata: Lacertidae) from the arid mountains of Pakistan. 24 records from Ostracoda abundance of Hole 48-406. 25 records from Updates to the bee fauna of Portugal with the description of three new Iberian Andrena species (Hymenoptera: Apoidea: Anthophila). 2 records from Encyocratella olivacea Strand, 1907, a senior synonym of Xenodendrophila gabrieli Gallon, 2003 (Araneae: Theraphosidae: Stromatopelminae) with a description of the male. 1021 records from UTEP Herpetology Osteology (Arctos). 2072 records from Vertical distribution of meiofauna in the North Sea and the Westerschelde estuary in 1993 and 1994. 10894 records from The Scottish Squirrel Database. 16 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 2 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 30 records from (Tab. 10) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-303A, Japanese Magnetic Lineations east of Japan. 6 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 1 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 1 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 1 records from Collection Crustacea - KAUMM. 2256 records from Benthos, zoo- and phytoplancton data collected during the monitoring cruise of RV "Vladimir Parshin" in 1996.. 254 records from FBIP: Baboon spider distribution records from selected South African museums. 52 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 22 records from Données du naturaliste Tillier Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 16 records from A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species. 13 records from Coccolith counts of multinet SO119_MSN1301. 2438 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 1023 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 7 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 31965 records from UWBM Mammalogy Collection (Arctos). 71 records from Planktic foraminifera abundance of Hole 32-313. 869 records from Royal Ontario Museum Fungarium (TRTC). 165 records from El código de barras de las especies NOM-059 de mamíferos del Noroeste de México. 41 records from Notes on the shrimp genus Palaemon Weber, 1795 (Crustacea, Decapoda, Palaemonidae) and related genera from Taiwan. 5601 records from Plant specimens of Horaiji-san Museum of Natural History. 79123 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 6 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 5445 records from Données bibliographiques et opportunistes Odonates issues du SIRF. 461 records from Benthic foraminifera counts of sediment core GIK23342-6. 20 records from Synopsis of the parasitoid wasp genus Cotesia Cameron, 1891 (Hymenoptera: Braconidae: Microgastrinae) in Australia, with the description of seven new species. 17628 records from Mammals housed at MHNG, Geneva. 7 records from Löydös Open Invasive Alien Species Observations. 777 records from Mammal osteology MZS. 10 records from Sediment properties of core PLG95B_01BOXG. 1366 records from Swiss Psyllid (Hemiptera) Collections - Basel. 1 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 4 records from Bemerkungen zu der Gattung Elasmognathus F ,, 1844, und Beschreibung einer neuen Art (Hemiptera: Heteroptera: Tingidae). 338 records from Planktic foraminifera abundance of Hole 15-148. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 95 records from UWIZM Mantodea. 218 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 28 records from Microplankton counts and carbon biomass at station TT008_5-CTD61. 5 records from Validation of the status of a species with high CO 1 and low nuclear genetic divergences: the scab mite Caparinia ictonyctis stat. res. (Acariformes: Psoroptidae) parasitizing the African hedgehog Atelerix albiventris. 44 records from Taxonomía y prospección del hábitat de las poblaciones de Bursera sect. Bullockia con especial énfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 204 records from données bibliographiques diverses (non araignées). 3 records from Description of the female of the cellar spider Mesabolivar guapiara (Araneae, Pholcidae) from Mata Atlântica, Brazil. 749 records from UNM Earth Sciences Collection (Arctos). 679 records from Phenological Center - Plants (Murmansk). 1 records from Neue Arten der Gattung Ypsiloncyphon KLAUSNITZER, 2009 (Coleoptera, Scirtidae) aus der Orientalischen Region II (215. Beitrag zur Kenntnis der Scirtidae). 1518 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 35 records from Taxonomy of Ecuadorian water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae). 137 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 95 records from Nannofossil abundance of Hole 22-217. 487 records from Bird specimens of Komatsu City Museum. 83 records from Total foraminifera counts of multinet M21/5_MSN728. 6402 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 1 records from Revision of the subgenus Orphnus (Phornus) (Coleoptera, Scarabaeidae, Orphninae). 12 records from A survey of Phrurolithidae (Arachnida: Araneae) in southern Caucasus, Iran and Central Asia. 1 records from A new species of Paratelmatobius (Anura: Leptodactylidae: Paratelmatobiinae) from the Atlantic Forest of southern Brazil. 60 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 7 records from Three new species of the genus Neuquenaphis (Hemiptera, Aphididae, Spicaphidinae) from southernmost South America. 3 records from Three new species of moth flies (Diptera, Psychodidae, Psychodinae) from the Afrotropical Region. 4 records from Description Of A New Species Of Pterostichus Bonelli, P. barri, From The Appalachian Mountains (Coleoptera: Carabidae). 39 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 2 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 400 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 3 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 1 records from A new species of Orthosiphon (Lamiaceae) from Angola. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 106 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 1 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 54 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 3 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 7 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 2193 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 4 records from A review of the ant genus Metapone Forel from Madagascar.. 82 records from Nannofossil abundance of Hole 20-200. 1 records from New species and additional records of Cephalocousya and Drepasiagonusa from China and Russia (Coleoptera: Staphylinidae: Aleocharinae: Oxypodini). 40 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 3068 records from The Vascular Plants Collection of the University of Goettingen. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 2 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 1488 records from Flora vascular acuática de la cuenca del Río Tamesí. 21 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 375 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 22 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 4962 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 501 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 2 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 5 records from Type locality records of Polycystididae species in the world. 513 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 101 records from Andes to Amazon Biodiversity Program. 3857 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 774 records from Données naturalistes de Stéphane ORIO. 49 records from Inventario herpetofaunístico del noroeste de Hidalgo. 379 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 9366 records from ZooplanktonBeaufortSeaNOGAP2. 6 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 81 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 172 records from Hermit crabs of the family Parapaguridae (Crustacea: Decapoda: Anomura) from Australia: species of Strobopagurus Lemaitre, 1989, Sympagurus Smith, 1883 and two new genera.. 164 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 12 records from Microzooplankton abundance and biomass at station NBP97-08-23-6. 98 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 2 records from A taxonomic review of the genus Triscaedecia (Lepidoptera: Alucitidae) in the world fauna. 1 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 28 records from Jardín Botánico Atlántico, Gijón: JBAG. 36 records from Microzooplankton abundance and biomass at station TT045_26-3. 2 records from Redescription of Pterygoplichthys punctatus and description of a new species of Pterygoplichthys (Siluriformes: Loricariidae). 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 178 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 587 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 115 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 523 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 106 records from Planktic foraminifera abundance of Hole 94-611. 3 records from Abundance of zooplankton in the Aral Sea. 33 records from Fish Fauna of Berlin. 3 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 1389 records from Phytoplankton abundance in surface water during cruise CD61. 1286 records from Kherson State University herbarium (KHER), Department of Botany. 29 records from Total foraminifera counts of trap L3_92_45. 161 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 3087 records from Nijmegen Natural History Museum (NL) - Herbarium. 407 records from The Sphecid wasps of the genus Cerceris LATREILLE, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from Subsaharan Africa and Madagascar, with description of five new species (Hymenoptera, Apoidea, Crabronidae). 35 records from Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: IV. Infraorder Anomura: Superfamilies Chirostyloidea, Galatheoidea, Hippoidea and Paguroidea. 925831 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 7313 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 106 records from Total foraminifera counts of trap L2_92_A42. 25 records from MIRC NAVFAC Incidental Sightings - Vessel 1965-2014. 31 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 8 records from Review of the genus Paradonus Stibick, 1971 (Elateridae: Negastriinae), with three new North American species. 38974 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 52 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 183 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 50 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2038 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 33419 records from WADFW PSAMP W1993. 1 records from Hyobanche thinophila (Orobanchaceae), a new species from the Western Cape of South Africa. 7 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 111 records from University of Algarve and ICNB Cetacean Sightings 1999. 56 records from Annales de la Société entomologique de France [1832- ]. 44 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 79921 records from Hymenoptera specimen database of Kyushu University. 200 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 1 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 269 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 172496 records from Finnish Floristic Database (Literature Sources). 34 records from The Myriapoda Collection of the National Museum of Nature and Science. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1278-1. 1 records from Review of the genus Elasmostethus (Hemiptera: Heteroptera: Acanthosomatidae) from the Korean Peninsula. 1053 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B. 14720 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1719 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 4 records from Microplankton counts and carbon biomass at station TT011_4-CTD46. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 50477 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 8 records from Conservatoire Botanique Pierre Fabre. 117 records from Nannofossil abundance of Hole 41-366A. 8 records from Bohemannia auriciliella (Nepticulidae) specimen data. 1365 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 9 records from A contribution to the knowledge of the prominent moths (Lepidoptera, Noctuoidea Notodontidae) of the Maputo Special Reserve with descriptions of four new species. 2 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 1447 records from Relative abundances of twenty-eight dominant benthic foraminifera species of DSDP Hole 23-219 (Table 1s). 30 records from Collection Crustacea - ZSRO. 682 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 1554 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 901 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 2 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 1 records from Two new species of snailfishes of the genus Careproctus (Cottoidei: Liparidae) from the western North Pacific Ocean with a range extension of Careproctus brevipectoralis. 1144 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 4 records from Four new species of the genus Diaphorus (Diptera: Dolichopodidae) from China. 3 records from American Asteraceae-feeding Astrotischeria species with a highly modified, three-lobed valva in the male genitalia (Lepidoptera, Tischeriidae). 166 records from Données coléoptères de l'Association des Entomologistes de Picardie. 1232 records from (Table 1) Planktonic foraminifera community at DSDP Hole 94-608. 18 records from A revision of Japanese Torymus Dalman (Hymenoptera: Torymidae). 106 records from Total foraminifera counts from multinet M31/2_MSN890. 2535 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 1018 records from CNAN/Araneae. 1 records from Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae). 10887 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 487 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 79 records from A revision of the shield-back katydid genus Neduba (Orthoptera: Tettigoniidae: Tettigoniinae: Nedubini). 20 records from Taxonomic review of the Hyphessobrycon panamensis species-group (Characiformes: Characidae). 372 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 21 records from Species of Ancistrus (Siluriformes, Loricariidae) from Ecuador, with the description of a new species from the Amazon River Basin. 472 records from Crustáceos macrobénticos de la plataforma y talud continental del Golfo de México. 1 records from Validation of Tethya samaaii Ribeiro & Muricy, 2011, replacement name for the sponge Tethya rubra Samaai & Gibbons, 2005 (Demospongiae, Tethyida, Tethyidae). 126 records from Revision of the Oriental Chaetocnema species (Coleoptera, Chrysomelidae, Galerucinae, Alticini). 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 1460 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 27 records from Marine algal (seaweed) flora of Terceira Island, Azores. 368 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 228 records from (Table 3) Planktonic foraminifer abundance of ODP Hole 162-980A. 143 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 21 records from A review of the Barsine obsoleta species-group with description of a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 55 records from The Stephanidae (Hymenoptera) of Mexico, with description of six new species and key to western Foenatopus Smith. 4 records from (Table 1) Biometrics and lipid content of polar bear (Ursus maritimus) adipose tissue between 1991-2007. 60 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 278 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 13 records from Benthic macrofauna abundance of sediment core 13200-047. 231 records from Epifauna community at Waarde and Saeftinghe (Westerschelde) in 1991. 2 records from Revision of the Palaearctic and Oriental species of the genus Oides Weber, 1801 (Coleoptera: Chrysomelidae: Galerucinae). 73579 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 99 records from Planktic foraminifera abundance of Hole 28-265. 1 records from Four new and one newly recorded species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Vietnam, with redescription of the little known species Diduga haematomiformis van Eecke, 1920. 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 456 records from Bird collection Natuurmuseum Brabant, Tilburg. 45490 records from Amphibiens et Reptiles de France métropolitaine (Enquête 1). 77 records from Benthic foraminifera abundance of Hole 42-372. 827 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 13986 records from Natural England Marine Monitoring surveys. 705 records from Range table from benthic foraminifers in ODP Hole 139-857A. 81 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 1148 records from Les spermaphytes de l'Herbier du Centre National de Floristique de Côte d'Ivoire: deuxième partie.. 5 records from A new species of the genus Protopolybia Ducke, 1905 (Hymenoptera, Vespidae, Polistinae), with taxonomic contributions to the exigua species-group. 91 records from Taxonomic revision of Agraphydrus Régimbart, 1903 I. China and Taiwan (Coleoptera: Hydrophilidae: Acidocerinae). 2202 records from Ground Beetle Recording Scheme - data verified via iRecord. 126 records from Foraminifera species abundances from tow TT011_10-MOC71. 10 records from Four new species and further contributions to the Leuctridae (Plecoptera) of the Korean Peninsula. 2520 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/12. 1 records from Dima spicata Schimmel, 1999 (Elateridae: Dimini), a morphologically remarkable species endemic to China. 8189 records from (Appendix A) Abundances of planktonic foraminifera in mid-Pleistocene sediments of ODP Site 184-1144 in the South China Sea. 242 records from (Table 1) Bottom fauna Metazoa in grab samples from the Namibia shelf in the area of Benguela upwelling. 4 records from Leptoclinides (Ascidiacea, Didemnidae) from Brazil: new records and two new species. 75 records from Range table from planktonic foraminifers in ODP Hole 170-1040B. 62 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 1 records from Taxonomic studies on the genus Orancistrocerus van der Vecht, 1963 (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 1 records from Definition of the Gonioctena subgeminata species group (Coleoptera, Chrysomelidae, Chrysomelinae), with descriptions of two new species from China and Vietnam. 10 records from Microzooplankton abundance and biomass at station TT050_7-9. 972 records from Coleoptera Collection. 59 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 131 records from Kangawalla Bird Sightings. 7 records from Michigan Plecoptera (Stoneflies): Distribution Patterns And An Updated Species List. 82 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 5 records from Four new species and new records of Manota (Diptera: Mycetophilidae) from Sulawesi, Indonesia. 371 records from Planktic foraminifera and paleoclimate temperature and salinity calculations from sediment core M44/1 GeoTü KL71. 580 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 13 records from Description of five new species in the genus Phlyctinus Schoenherr (Coleoptera, Curculionidae): a first step in deciphering the P. callosus complex. 1 records from A unique new genus and species of the phyline plant bug tribe Hallodapini from the Philippines and Thailand (Hemiptera: Heteroptera: Miridae: Phylinae: Hallodapini). 1 records from Description of a new species of Ochraethes Chevrolat, 1860, redescription of Plocaederus mirim Martins and Monné, 2002, and new geographical records for Plocaederus Dejean, 1835 (Coleoptera, Cerambycidae, Cerambycinae). 18 records from Annotated list of Mimallonidae (Lepidoptera, Mimallonoidea) from Trinidad and Tobago, with the description of a new species of Cicinnus Blanchard, 1852 and taxonomic notes. 12511 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 6014 records from Florida Manatee Synoptic Aerial Survey 1991-2019. 5 records from DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 1550 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Georgyi Ushakov" in 1992”. 395037 records from Welsh Invertebrate Database (WID). 2679 records from Bulletin mensuel de la société linnéenne de Lyon [1932- ]. 671 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part II. 2 records from Four New Bat Species (Rhinolophus hildebrandtii Complex) Reflect Plio-Pleistocene Divergence of Dwarfs and Giants across an Afromontane Archipelago. 2091 records from Dipterists Forum - Recording Scheme - Stilt & Stalk Flies. 1 records from First Australian records of Ethusina (Crustacea: Decapoda: Ethusidae) and additional records from New Zealand. 6894 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Scorff river (France). 8 records from Miscophus Jurine, 1807 (Hymenoptera, Crabronidae) in Central, Northern, and Eastern Europe. 1116 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 564 records from Benthic foraminifera abundance of Hole 56-435. 2 records from Microzooplankton abundance and biomass at station TT054_21-15. 17 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 42 records from Rainforest and cloud forest Scolytodes (Curculionidae, Scolytinae, Hexacolini) from the Arthropods of La Selva inventory in Costa Rica: new species, new synonymy, new records. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from Planktic foraminifera abundance of Hole 19-185. 189 records from Oceanic Society's Marine Mammal Sightings in Belize 1992 - 2011. 2 records from One new species and one newly recorded species of Cyllodes Erichson from China (Coleoptera: Nitidulidae: Nitidulinae). 46 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 14 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 488423 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 2 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 16 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_276-1. 1 records from Colección de macroalgas de la costa Argentina (IADO-UNS-CONICET). 8 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 4 records from A Catalogue and Historical Study of the Odonata of Ecuador. 136 records from Planktic foraminifera abundance of Hole 94-610. 116 records from Biodiversity of the Desna river valley and its tributaries. 51508 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 25 records from (Table 5) Abundance of selected helicoliths at DSDP Site 82-563 in the North Atlantic. 9 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 32 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 329690 records from KTP Ring Data. 39 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 1 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 283 records from Flux data of NU2_trap (Table A1). 8 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 1 records from Ground spiders (Araneae: Gnaphosidae, Liocranidae, Prodidomidae) from the Greek islands Rodos, Symi and Karpathos, with the description of new species. 1658605 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 9 records from Capobula gen. nov., a new Afrotropical dark sac spider genus related to Orthobula Simon, 1897 (Araneae: Trachelidae). 2 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 158 records from Bishop's University Insect Collection (BUIC). 7 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 48406 records from BioFokus. 2 records from Anymals+plants - Citizen Science Data. 1233 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 41 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 861 records from Planktic foraminifera abundance of Hole 23-219. 25846 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1079 records from CNAN/Scorpiones. 60 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 94 records from Total foraminifera counts of multinet M26/1_MSN845. 234 records from Pollen analysis of sediment profile BLA00 from Blankensee. 5912 records from NCSM Non-molluscan Invertebrates Collection. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 301 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 103780 records from The AAU Herbarium Database. 5 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 1 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 696 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 10 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 2524 records from Colecção Entomológica do Museu de História Natural de Maputo. 1 records from A new species of Umanella Gauld (Hymenoptera, Ichneumonidae) from Ecuador. 11 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 188 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 24 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 343 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 26 records from Craigellachie NNR invertebrate records compiled from SNH files. 240 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 1 records from Hydrographic profiles in South West Atlantic Ocean derived from Southern Elephant seals dives. 1125 records from Collection Polychaeta - ZSRO. 69359 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 139 records from Nannofossil abundance of Hole 55-433. 8 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 796 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 15 records from Revalidation and taxonomic revision of Teloneria Aczél (Diptera, Neriidae), with description of two new species. 49 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 1 records from New species of black corals (Cnidaria: Anthozoa: Antipatharia) from deep- sea seamounts and ridges in the North Pacific. 243 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 4 records from Freshwater fish records via iRecord - additional species. 61 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 20 records from Abundance of benthos infauna at station GIK23055-1. 3 records from A new species of phlebotomine sandfly, Pintomyia (Pifanomyia) duckei (Diptera: Psychodidae) from Manaus, State of Amazonas, Brazil. 3 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 15 records from A new species of Anchoviella Fowler, 1911 (Clupeiformes: Engraulidae) from the Amazon basin, Brazil. 4 records from Drosera quartzicola (Droseraceae), a new and threatened species from the Serra do Cipó, Brazil. 6 records from Benthic macrofauna abundance of sediment core 13200-017. 126 records from SJRP-Fungi - Herbário de fungos de São José do Rio Preto. 6 records from Synonymies, a new combination, and four new species in Amphicnaeia Bates (Coleoptera: Cerambycidae: Lamiinae). 551 records from Gunma Museum of Natural History, Fungi Specimen. 45 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 2 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 5 records from Revision of the non-marine centric diatom flora (Bacillariophyta) of the sub-Antarctic Campbell Island (southern Pacific Ocean) with the descriptions of five new species. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 6 records from Qarshi Botanical Garden. 1620 records from (Table 2) Pleistocene nannofossil range chart for ODP Hole 134-828A. 4159 records from Plant specimens of Horaiji-san Museum of Natural History Kichi T. collection. 10 records from Nannofossil abundance of Hole 15-146A. 1 records from Three new species of the cutthroat eel genus Dysomma, with comments on the variation of D. taiwanense (Anguilliformes: Synaphobranchidae). 4 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1335. 189378 records from PIROP Northwest Atlantic 1965-1992. 3 records from The oribatid mite genus Topalia in Australia (Oribatida: Nosybeidae) and the taxonomic status of related families and genera. 102 records from Organochlorine and total mercury in bivalve Anadara tuberculosa and other species from the Nicoya Gulf, Costa Rica in 1988. 4080 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 46 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 104196 records from UWFC Ichthyology Collection. 70 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 646 records from Auburn University Museum of Natural History Invertebrates. 3 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 190 records from The ultor - group of the genus Dolichogenidea Viereck (Hymenoptera, Braconidae, Microgastrinae) from China with the descriptions of thirty-nine new species. 987 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 7 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 4 records from Notes on Allium section Rhizirideum (Amaryllidaceae) in South Korea and northeastern China: with a new species from Ulleungdo Island. 16515 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 352 records from (Table 5) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841A. 17 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 307 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 16230 records from CUMV Fish Collection. 2138 records from MUST, Insecta. 112 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 23 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 262884 records from Données ONF faune-flore-fonge. 1103 records from Collection entomologique Pierre Lachiver. 10 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 1 records from ZUEC-POP - Coleção de Polyplacophora do Museu de Zoologia da UNICAMP. 14 records from Stenus maculifer CAMERON: eine Büchse der Pandora (Coleoptera, Staphylinidae) 365. Beitrag zur Kenntnis der Steninen. 19853 records from University of Tennessee Fungal Herbarium. 1375 records from University of Michigan Museum of Zoology, Division of Mollusks. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 271 records from Flora ficológica de la huasteca potosina. 126 records from Range table from benthic foraminifers in ODP Hole 144-874B. 56 records from Données acquises via le réseau du Conservatoire botanique national du Bassin parisien. 113 records from Type Specimen Database of Museum and Institute of Zoology PAS. 57545 records from DASSH Data Archive Centre Academic Surveys. 1359 records from Herbier de Wallis et Futuna. 12 records from Annotated type-catalogue of Brachyura (Crustacea, Decapoda) of the Muséum national d’Histoire naturelle, Paris. Part II. Gecarcinidae and Grapsidae (Thoracotremata, Grapsoidea), with an Appendix of pre- 1900 collectors. 5 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 8085 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 7 records from Subspecies of Pleurota bicostella (Clerck, 1759) revisited and descriptions of nine new species in the P. bicostella species group (Lepidoptera: Gelechioidea Oecophoridae: Pleurotinae). 462 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 23 records from Morphologische Daten von Natrix. 4 records from Taxonomic revision of the epigean representatives of the spider subfamily Harpacteinae (Araneae: Dysderidae) on the island of Crete. 1011 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 2 records from Hypsipyrgias joseliae, a new species of lace bugs (Heteroptera: Tingidae: Tinginae) from New Guinea with a key to species of the genus Hypsipyrgias, and comments on three allied genera Hypsipyrgias Kirkaldy, 1908, Diplocysta Horváth, 1925, and Hypsotingis Drake, 1960. 17 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 6 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 6050 records from Happywhale - Humpback Whale in North Pacific Ocean. 216 records from LISU Herbario Angola. 3290 records from CNAC/Coleccion Nacional de Acaros. 130 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 352 records from hauterivian_echinoids_of_the_paris_basin. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 45 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 90 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 3 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 3 records from Contributions to the knowledge of Atlantic Canadian Histeridae (Coleoptera). 228 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 1272 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 22719 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 4436 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 970 records from MCP-Mamiferos - Coleção de Mamíferos. 11 records from Benthic macrofauna abundance of sediment core 12930-073. 336 records from Stable isotope data and sedimentology of core SO42-74KL. 41 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 82 records from Meniscus Midges (Dixidae) of Ireland. 2 records from A new species of the genus Tagasta Bolivar, 1905 (Orthoptera: Pyrgomorphidae) from India. 30078 records from Swiss National Bat Databank: Regional Coordination Western Switzerland (CCO). 63213 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 3145 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 19 records from Sierraperla Jewett, 1954 (Plecoptera: Peltoperlidae), Distribution, Egg Morphology And Description Of A New Species. 116 records from Zambian Bat Collections Worldwide. 4 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 4 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 14176 records from Vascular plants of south-central China. 79 records from Entomological collection of the National Museum. 208 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 48 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 1 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 3 records from Review of the Taiwanese Laccobius Erichson, 1837 (Coleoptera: Hydrophilidae) with description of a new species. 2070 records from Helmintos parásitos de peces del sureste de México. 260 records from Range table from benthic foraminifers in ODP Hole 159-959A. 396 records from Radiolaria assemblage in sediment core GIK23259-2. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 268 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 58 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 310 records from Données naturalistes de Hervé BOUYON. 676 records from Données de la collection Rousset -1947-2013. 1 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 57 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 25 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 109 records from Total foraminifera counts of multinet M21/2_MSN629. 90 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 138 records from Total foraminifera counts of multinet POS247/2_MSN1372. 1 records from Dinoflagellate abundance of Hole 85-572C. 26 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 38 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 658 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 5 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 39 records from 1994-2020 Capercaillie Cold Searches Data, Scotland. 62 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 710 records from RNF - Données du Parc Naturel Régional du Vercors. 1482 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 1314 records from Insectes Hyménoptères Scollidés de France. 1 records from Redescription of the type specimens of Althepus pictus Thorell, 1898 (Araneae Psilodercidae) from Myanmar. 1441 records from Family Geraniaceae in CSBG SB RAS herbarium collections (NS, NSK). 10 records from Revision of the Metallactus generosus species-group with a preliminary evaluation of the effectiveness of the endophallus morphology in distinguishing critical sibling species (Coleoptera: Chrysomelidae: Cryptocephalinae). 350 records from The hoverfly collection (Diptera, Syrphidae) of the International Institute of Tropical Agriculture (IITA) at Calavi (Benin). 4717 records from Weddell Sea macrozoobenthos EASIZ I. 736 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 1 records from Redescription of larva of the South African endemic dobsonfly genus Chloroniella Esben-Petersen, 1924 (Megaloptera, Corydalidae), with a proposed terminology for Corydalidae larval sclerites. 610 records from IOW Natural History & Archaeological Society Marine Records. 18 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 11 records from Contribution to the knowledge of the genus Cordilura Fallén (Diptera, Scathophagidae) from Japan, with descriptions of three new species. 2 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 140 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 78 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 3 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 3 records from Données de NICOLAS Vincent (SAPROX). 15 records from Benthic macrofauna abundance of sediment core 13201-002. 12 records from (Table S1) Nannofossil abundances at DSDP Hole 86-577. 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 614 records from Planktic foraminifera assemblage of sediment core ELT49.023-PC. 52 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part II. 77 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 3 records from The larva of Lestes alfonsoi Gonzalez & Novelo (Zygoptera: Lestidae). 9 records from Planktic foraminifera abundance of Hole 14-144. 5 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 2 records from A new species in the genus Alopecosa Simon, 1885 from Korea (Araneae: Lycosidae). 530 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 787 records from Heliconiine Butterfly Collection Records from University of Cambridge. 1 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 2 records from Description of Harpactea popovi sp. n. from Bulgaria with further taxonomic notes on related species (Araneae, Dysderidae). 16 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 98 records from Planktic foraminifera counts at CTD station PS55/078-1. 8 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 7373 records from Fish specimens of Toyama Science Museum. 63 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 121 records from Range table from ostracoda in ODP Hole 143-866B. 5 records from Anderemaeus (Acari, Oribatida) - overview, three new species from South America and reassessment of Anderemaeidae supported by ontogeny. 880 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru. 225 records from Colección Limnológica Universidad de Antioquia. 20 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 667 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 57697 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 68 records from Conservación y monitoreo de anfibios en riesgo de extinción en Chiapas. 5210 records from Données naturalistes de LUPOLI Roland. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 33 records from A new species of Aframomum (Zingiberaceae) from Central Africa. 130 records from Catopsilia butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 19569 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 8 records from A new species of the genus Tetragonopterus Cuvier, 1816 (Ostariophysi: Characiformes: Characidae) from the rio Tocantins drainage, Brazil. 276 records from Carabidae of the European North-East of Russia. 3691 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 2 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 74 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 12 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 5 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 1924 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 12 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 60 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 6 records from Abundance of benthos infauna at station GIK23065-1. 14728 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 4 records from Planktic foraminifera abundance of Hole 17-166. 1265 records from Benthic foraminifera abundance of Hole 84-570. 1074 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 3 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 12537 records from University of Nebraska State Museum Fish Collection. 9 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 6 records from A revision of Cinnadenia Kosterm. (Lauraceae). 2452 records from Colección de Zoología Invertebrados - Helmintología. 5219 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 64 records from Planktic foraminifera assemblage in sediment core SU90-I06. 25 records from Nineteen new species of Alycaeidae from Myanmar and Thailand (Gastropoda: Caenogastropoda: Cyclophoroidea). 79 records from Total foraminifera counts of multinet POS247/2_MSN1384. 5296 records from Fishes of INEP and NFH collections. 108861 records from Terrestrial and limnic invertebrates systematic collection, NTNU University Museum. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 21 records from Museo Argentino de Ciencias Naturales (MACN), Buenos Aires: sea stars collection (Asteroidea, Echinodermata). 1 records from Four new species of Parajapyx (Diplura: Parajapygidae) from Mexico with redescription of Parajapyx isabellae aztecus Silvestri. 20 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 256 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 5 records from The Resin and Carder bees of south India (Hymenoptera: Megachilidae: Anthidiini). 47 records from A taxonomic revision of the genus Xylota Meigen (Diptera: Syrphidae) in Korea. 1 records from Four new genera of Schizopteridae (Hemiptera: Heteroptera) from theAfrotropical and Neotropical regions. 6 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 547 records from Magnoliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 40 records from Review of the mirine plant bug genus Eurystylus Stål from Japan and Taiwan (Hemiptera: Heteroptera: Miridae: Mirinae), with descriptions of two new species, a new synonymy and a new combination. 73 records from Survey of slender naiad, Najas flexilis, in Loch of Butterstone and Loch of Craiglush. 1 records from A new pygmy species of box jellyfish (Cubozoa: Chirodropida) from sub-tropical Australia. 167 records from Morfología funcional de mantos de rodolitos en el golfo de California, México. 392 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 115-708A. 12 records from ZUEC-CNI - Coleção de Cnidaria do Museu de Zoologia da UNICAMP. 136 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/042-2. 348 records from The Golden wasps collection (Chrysididae) at the Staatliches Museum für Naturkunde Stuttgart. 3190 records from MUFAL herbarium - Museu de História Natural da Universidade Federal de Alagoas - Herbário Virtual REFLORA. 5146 records from Banco de datos de la ictiofauna del Río Bravo desde 1902 a 1992 en la colección ictiológica de la UANL. 5033 records from Montana State University - Billings. 5 records from Contribución a la distribución, ecología y estado de conservación de dos especies del género Sceloporus, endémicas de la región del Cabo, Baja California Sur. 479 records from Geochemistry and sedimentology on core POS200/10_28-1. 415 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 34733 records from Oskarshamn herbarium (OHN). 539 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica Tapachula). 3960 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 7842 records from Batsites inventory for England (1949-2011). 297 records from Abundance of calcareous dinoflagellates of sediment core GeoB1214-1. 56684 records from Isopoda (Interim dataset). 1 records from Records of Wenchengia (Lamiaceae) from Vietnam. 353 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 1609 records from Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 202 records from Planktic foraminifera counts of sediment core RC14-7. 1 records from A New Genus and Species of Clingfish (Teleostei: Gobiesocidae) from Western Australia. 729 records from Algae collection, Oslo (O) UiO. 8637 records from Relative abundance of benthic foraminifera in sediment core M5/2_KL15. 29 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 1585 records from Données naturalistes de Jean-Paul LECHAPT. 3 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 1 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 55 records from Planktic foraminifera abundance of Hole 16-161. 17499 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 6 records from Guinea-Bissau Herpetological Collection - IICT. 322 records from Inventaire des Odonates. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 23 records from Synopsis of the bee genus Thygater Holmberg 1884 (Hymenoptera, Apidae) in the Brazilian state of Minas Gerais, with the description of a new species and a key to all Brazilian species. 4 records from Planktic foraminifera abundance of Hole 19-184B. 246 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 191 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 3360 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 13956 records from Lepidoptera specimen database of Japan. 1516 records from Leicestershire and Rutland Reptile Records to 2011. 38 records from Smear slide analysis on sediment core GeoB4214-1. 37 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 115 records from Collection Vermes - ZMB. 621 records from Culture Collection of Algae. 273 records from Planktic foraminifera abundance of Hole 68-503B. 17066 records from VIES herbarium - Universidade Federal do Espírito Santo - Herbário Virtual REFLORA. 6213 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947). 22 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 536 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 53 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 144 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 1 records from Glossostyles perspicua gen. et sp. nov. and other fungivorous Cecidomyiidae (Diptera) new to the Czech and Slovak Republics. 8 records from New genera for species of Jassa Leach (Crustacea: Amphipoda) and their relationship to a revised Ischyrocerini. 3 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 475 records from (Table 2) Raw counts of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 17 records from Coccolith counts of multinet SO119_MSN1272. 273 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 9 records from New species of Condylostylus Bigot (Diptera: Dolichopodidae) from Comoros Madagascar, Tanzania and South Africa, with key to Afrotropical species. 1691 records from Butterflies of Singapore and Peninsular Malaysia (Nymphalidae). 6836 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 32783 records from FUEL - Herbário da Universidade Estadual de Londrina. 90 records from Atlantic Forestry Centre Insect Reference Collection. 7645 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 58 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 52 records from Range table from planktonic foraminifers in ODP Hole 139-855A. 794 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 12156 records from WADFW PSAMP S1992. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 2357 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 96 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 34 records from Planktic foraminifera abundance of Hole 63-472. 168 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 8 records from First report of the old world genus Pelecystola in North America, with description of a new species (Lepidoptera, Tineidae). 1180 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 1381 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 298 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 99 records from Institut Mediterrani d'Estudis Avançats (CSIC-UIB): IMEDEA-OTO. 14648 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 27033 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 4 records from New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 206 records f
Keywords: GBIF; biodiversity; species occurrences